Improving EFL pronunciation and self-concept among non-English-major Chinese learners: a proposal / Zhang Xin, Asmaa AlSaqqaf and Wardatul Akmam Din - Xin, Zhang; AlSaqqaf, Asmaa; Din, Wardatul Akmam (Akademi Pengajian Bahasa, 2021)
The pronunciation of most English-as-a-foreign-language (EFL) Chinese learners is reported to be inaccurate. Meanwhile, relevant literature suggests that emotional factors such as positive self-concept can help enhance language learning. Therefore, exploring the target language (TL) pronunciation self-concept is of practical significance to improve the TL teaching and learning. Very limited research has been conducted to explore the English pronunciation and self-concept of EFL non-English major learners in China. Therefore, this paper presents a proposal that attempts to address this research gap by exploring the effect of an intervention that is designed to improve the English pronunciation of EFL non-English-major Chinese learners in a public university in China. The study will employ a quasi-experimental design to collect data through implementing the intervention. At the same time, a longitudinal survey will be distributed to the research sample to investigate their English pronunciation self-concept before and after the intervention. Two classes representing the control group and the experimental group will participate in the study. The control group will be taught according to the in-situ methods, while the experimental group will receive the English pronunciation intervention. Additionally, a pre-test and post scores will be analyzed to investigate the effect of the intervention on the participants’ EFL pronunciation as well as their self-concept of English pronunciation. It is hoped that this study will shed more light on the TL pronunciation self-concept as well as on the teaching techniques recommended to improve EFL pronunciation among EFL Chinese learners.